Using commercial enzyme immunoassay for measuring pregnancy-associated glycoproteins to diagnose pregnancy in dairy cows under field conditions in Algeria - Abdelhanine Ayad (RUDN Journal of Agronomy and Animal Industries, 2021)
The purpose of the present work was to study effectiveness for early pregnancy diagnosis in cattle of the new enzyme immunoassay (EIA) sandwich kit commercially available based on the measurement of pregnancy-associated glycoproteins (PAGs). 120 Holstein-Friesian cattle of mixed age and parity were comprised from different dairy herds. The pregnant females (n = 68) were diagnosed by ultrasonography at day 35-40 after artificial insemination and confirmed by transrectal exploration at 2-3 months after AI. The non-pregnant females (n = 52) were housed in the absence of males during the experimental period. Blood samples were collected from coccygeal vessels of females into EDTA tubes. The serum was obtained by centrifugation and the serum was stored at - 20 C until assay. The PAG concentrations in pregnant and non-pregnant females were determined in serum by EIA kit. The reproducibility inter- and intra-assay of the PAG-EIA is satisfactory (2.78 and 13.19 %, respectively). The accuracy ( 94.8 %) and the test of parallelism were largely acceptable. No cross-reaction was observed with the different hormones tested at different dilutions. PAG-EIA system gave 100 % sensitivity and negative predictive values. Whereas, specificity and positive predictive value were 91.93 and 71.15 %, respectively. The accuracy of pregnancy diagnosis by PAG-EIA was 87.5 %. In conclusion, the present study shows clearly that the EIA kit can be used to measure PAG in serum cows for the detection of gestation in Algeria. Therefore, this alternative technique could be recommended to replace the radioactive methods in immunoassays to improve the reproductive performances and an efficient tool for reproductive management of dairy cattle.